Impact of Rural Road on Socio-economic Development of Otukpo and Agatu Local Government Area of Benue State - Obademi Agnes Olufunke; Chibuzo Nwokobia; Omale Onuh (Universitas PGRI Madiun, 2023)
The research aims to analyse the influence of rural roads on the socioeconomic development of Benue state's Otukpo and Agatu local government areas (LGAs). The survey method is used as the research strategy in this study. Traders, farmers, youth, and seniors who have resided in these locations for at least four (4) years are the target responders. The study included 400 participants. In this investigation, the random sampling approach was also used. Five rural villages were selected from each of the LGAs. Data was gathered from both primary and secondary sources. A questionnaire and interviews were the primary sources. Secondary sources included periodicals, textbooks, published or unpublished resources, and internet items that could not be retrieved through primary data. In this study, data was gathered using a questionnaire and an interview with structured questions (both open-ended and closed-ended). The instrument yield reliability coefficient is 0.07, and the data was presented in tabular form using frequencies and percentages. Rural development, according to this work, is the provision of basic amenities, infrastructure, increased agricultural production, extension services, and job creation for rural inhabitants. One of the most prevalent approaches to rural development used by developing nations across the world is infrastructure supply. The infrastructure proposed for rural development might be physical, social, or institutional. This work also suggested that the government construct suitable highways in conjunction with a private organisation in order to enhance the lives of rural inhabitants in the two local government regions and boost rural development in the area